Facilitators and barriers in the development and implementation of depression prevention and treatment policies in China: a qualitative study - Jinping Ma; Hai Zhou; Qinqin Fu; Guohua Lu (BMC, 2023)
Abstract Background Depression is one of the leading causes of avoidable suffering and premature death worldwide, leading to the disease burden among mental disorders. Depression-related deaths can be prevented by developing and implementing good depression prevention and treatment policies. The goal of this study is to provide theoretical direction and useful references for examining the outstanding service work of depression prevention and treatment. It also aims to describe how depression prevention and treatment policies were developed and put into practice in China, along with the associated facilitators and barriers. Methods We integrated two data sources using a case study approach: a document review of relevant policy documents, published articles and reports between 2004 and 2022 (N = 12 papers) and in-depth interviews (N = 41). Participants were drawn from pertinent sectors to managing depression: research and academia, relevant government departments, health care providers, people with depression and their families, and community organisations. Thematic analysis was used to analyse all data. Results A comprehensive programme of work exploring specific services for depression prevention and treatment was developed in China in 2020. Facilitators of policy development and implementation include (1) political commitment and strong leadership, (2) coordination mechanisms, (3) stakeholder enthusiasm and commitment, (4) resources, and (5) the use of digital technologies. The main barriers leading to delays in policy development and implementation include (1) insufficient awareness and lack of depression literacy, (2) lack of resources and (3) stigma and social discrimination (4) lack of united action. Conclusion Although the process of implementing a distinctive service programme for depression prevention and treatment in China has been long, the current policy is in line with current global efforts. Strategies to reduce Stigma and increase knowledge about depression are part of a national and international approach to reducing the burden of depression. Political commitment and the involvement of all stakeholders remain necessary. An adequate response to depression will require the involvement of society as a whole, with joint action to reduce the risk of exposure to adversity and enhance protective factors.